Conductive hydrogel based on dual-network structure with high toughness, adhesion, self-healing and anti-freezing for flexible strain sensor - Ya Wen; Ling Yi Zeng; Xin Chun Wang; Hong Mei Chen; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu (Next Materials)
The development of multi-functional hydrogels is necessary to meet the needs of flexible sensors in different application scenarios. A conductive hydrogel with high toughness, adhesion, self-healing and anti-freezing properties was prepared. The hydrogel was synthesized by in-situ polymerization of acrylic acid in glycerol hydrate solution system of gelatin and aluminum ion, and then cryogenically refrigerated. After low temperature treatment, the triple helix structure produced by the self-assembly of the gelatin in the hydrogel increases the cross-linking density of the hydrogel, and forms a double network with polyacrylic acid to improve its mechanical properties (stress up to 85.7 kPa, strain up to 1428 %). In addition, this triple helix structure can dissociate and recombine at different temperatures, and interact with other dynamic bonds (hydrogen bonds, Al3+ coordination) in the system, so that the hydrogel has excellent self-healing ability (healing rate up to 86.8 %). Because the system contains a large number of -OH, -NH2 and -COOH groups, it can adhere to the surface of various materials through hydrogen bonding. The free Al3+ makes the hydrogel obtain good electrical conductivity and strain sensitivity (GF=3.01), and the strain sensor assembled by it has a stable and accurate monitoring effect on the fine movements of human body such as various joint movements and pronunciation. Additionally, the presence of glycerol provides anti-freezing properties, ensuring flexibility and electrical conductivity even at low temperatures (-20 ◦C). This hydrogel is a promising candidate for intelligent wearable devices in extreme environments such as snow and ice sports.